"Krokodil" drug - Related osteonecrosis of midface: A case series. Issue 12 (December 2019) - Hakobyan, Koryun; Poghosyan, Yuri
Abstract: Krokodil is a cheap and effective home-made substitute for heroin. It is widely used over the territory of the former USSR (Russia, Ukraine, Armenia and others). Krokodil drug-related midface ON often occurs as a complication of maxillary ON. Treatment of Krokodil drug-related ON of the midface is challenging. It is difficult to determine the ON zone preoperatively and intraoperatively, due to the complex anatomy of the midface and the different periods of the disease onset in different areas. The aim of this study is to show variations of the clinical course and treatment options of Krokodil drug-related ON of the midface. In this study, 3 cases of Krokodil drug-related midface ON are reported. The main clinical feature of midface ON is extraoral fistula in the midfacial zone with purulent discharge or extraoral exposure of zygomatic bone. Surgery is the main treatment method for Krokodil drug-related midface osteonecrosis. Surgery includes necrotic bone removal and defect closure. Usually an extraoral approach is used to expose necrotic bone. Intraoral maxillary sinus floor defect is closed with the use of a buccal fat pad to prevent formation of oroantral communication. Drug withdrawal, radical necrectomy, and proper closure of formed defects are the main factors that lead to successful treatment of Krokodil drug-related midface ON patients.